Rumen degradation characteristics of the herbage mass samples and the simulated grazing samples for dairy cows - Pulido, Rubén; Leaver, John David (Pesquisa Agropecuaria Brasileira, 2000)
An experiment was carried out in order to describe the ruminal degradation characteristics of forages, in herbage mass samples (FD) and in simulated grazing samples (FS), obtained at two sward heights (high and low) from a permanent pasture (Lolium perenne L.). The degradation kinetics of the samples was studied using in situ dacron bags. Data collected were fitted according to an exponential equation. The soluble fraction (g/kg DM) of the dry matter (DM) (299 vs. 351, s.e.d.= 5.4), of the organic matter (OM) (304 vs. 376, s.e.d.= 3.3) and of the nitrogen (250 vs. 301, s.e.d.= 6.4) were significantly higher (P < 0.05) for simulated samples than for the herbage mass samples. The potential degradability (g/kg DM) of DM, OM and nitrogen was significantly higher on FS compared with the FD (P < 0.05). The effective degradability for the FS samples was greater than for FD samples, either for DM (474 vs. 508, s.e.d.= 13.0), OM (490 vs. 529, s.e.d.= 11.6), or nitrogen (351 vs. 419, s.e.d.= 10.0). A significant greater effect (P < 0.05) of the low sward height on the effective degradability was found for the nitrogen only.